PERAN FITRA RIAU DALAM MENDUKUNG KETERBUKAAN INFORMASI ANGGARAN KOTA PEKANBARU PADA TAHUN 2024 - Helmi, Syafiqah Suud; Wasillah, Asiah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2026)
Public information openness is a crucial issue amid the high incidence of corruption in Pekanbaru City. With public information openness, it is possible to achieve budget transparency, which serves as a strategic solution to promote accountable governance and strengthen community participation in public oversight. Therefore, the presence of Non-Governmental Organizations (NGOs) plays an essential role in bridging community interests to realize information openness. This study aims to analyze the role of the Indonesian Forum for Budget Transparency (FITRA) Riau in promoting budget information openness in Pekanbaru City. This study uses a qualitative approach with a descriptive research type. Data collection was conducted through in-depth interview techniques. Data analysis is operationalized through the stages of data reduction, data presentation, as well as conclusion drawing and verification. The theoretical framework used refers to Ismail Haddad's theory of NGO roles, which includes four indicators, namely motivator, communicator, dynamist, and facilitator. The research results reveal that FITRA Riau has implemented all four role indicators. As a motivator, FITRA Riau strives to increase public awareness and participation through a functional approach tailored to public needs. As a communicator, this institution bridges public aspirations to the government and facilitates interactive discussion spaces. As a dynamist, FITRA Riau mobilizes community potential through innovative programs based on budget analysis. Meanwhile, as a facilitator, FITRA Riau is recorded to actively organize budget school programs and provide assistance for information disputes at the Information Commission in the past period. . The conclusion of this study is that FITRA Riau, in principle, has carried out its role in advocating for budget transparency, but its implementation has not been optimal. The main inhibiting factors include the lack of intensity in institutional communication and the discontinuation of several strategic programs. Therefore, this study recommends that FITRA Riau redesign a more inclusive public communication strategy, ensure the sustainability of programs through strategic partnerships, and intensify technical assistance services for the community so that regional budget oversight can be effective. Keyword : The Role of NGOs, Budget Transparency, FITRA Riau.